Accounting of the Lease Contract according to the IFRS: the Current Status and the Prospects for the Russian Organizations - GULNARA I. Alekseeva (Учёт. Анализ. Аудит, 2019)
Lease of a property, plant and equipment under the conditions of market economy is a common form of the commercial relations. Many industrial enterprises which have real estate objects on their balance along with their core business are engaged in the so-called non-core types of activities - lease their rooms to other businesses for different purposes, like production, office, warehouses. For the organizations which don’t have the opportunity to purchase the property which is necessary for conducting economic activity, leasing property is one of the best solutions for them in such a situation. At the same time the organizations that present their reporting in the format of the IFRS are currently providing and disclosing in their financial reporting all the information regarding rent and leasing transactions according to the IAS17 “Lease”. On the 11th of August, 2016 the translation of the new standard of the IFRS16 “Lease” was published on the website of the Ministry of Finance of the Russian Federation. The organizations are obliged to apply this new standard starting from the first of January 2019. Therefore the new features and peculiarities of accounting of lease according to the existing IFRS and the expected changes are of interest both to accountants and to managers of the Russian organizations. The following methods of a research were applied in the article: observation, analysis and synthesis. The information presented in the article can be applied in practical work of accounts departments of the organizations, and also in the educational process in higher educational institutions.